2016
DOI: 10.1167/iovs.16-20671
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15–Induced Contractile Activity and Extracellular Matrix Production in Human Trabecular Meshwork Cells

Abstract: PurposeTo determine the role and regulation of growth differentiation factor-15 (GDF-15), a TGF-β–related cytokine in human trabecular meshwork (TM) cells in the context of aqueous humor (AH) outflow and IOP.MethodsRegulation of expression by external cues, and the distribution and secretion of GDF-15 by human TM primary cell cultures, and the effects of recombinant (r) GDF-15 on TM cell contractile characteristics, actin cytoskeleton, cell adhesion, extracellular matrix (ECM), α-smooth muscle actin (αSMA), SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…FNDC3B- a novel interactor of IFITM3 promotes cell migration by cooperating with ANXA2 96 . FNDC3B has been found to be upregulated in samples of hepatocellular carcinoma infected with HBV (Hepatitis B virus) or HCV and overexpressed in normal liver tissue infected with viral hepatitis 97 . It has also been reported that the expression of FNDC3B increases on induction of GDF-15 which is known to regulate expression of genes that orchestrate changes in cytoskeleton and adhesion junctions 97 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FNDC3B- a novel interactor of IFITM3 promotes cell migration by cooperating with ANXA2 96 . FNDC3B has been found to be upregulated in samples of hepatocellular carcinoma infected with HBV (Hepatitis B virus) or HCV and overexpressed in normal liver tissue infected with viral hepatitis 97 . It has also been reported that the expression of FNDC3B increases on induction of GDF-15 which is known to regulate expression of genes that orchestrate changes in cytoskeleton and adhesion junctions 97 .…”
Section: Discussionmentioning
confidence: 99%
“…FNDC3B has been found to be upregulated in samples of hepatocellular carcinoma infected with HBV (Hepatitis B virus) or HCV and overexpressed in normal liver tissue infected with viral hepatitis 97 . It has also been reported that the expression of FNDC3B increases on induction of GDF-15 which is known to regulate expression of genes that orchestrate changes in cytoskeleton and adhesion junctions 97 . In this respect, it is interesting to note that IFITM3 has been suggested to inhibit early stages of Zika virus infection by directly altering the properties of cell and/or viral membranes and blocking formation of fusion pores 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Very importantly, several authors have reported that commercially available GDF-15 preparations are often contaminated with variable bioactive levels of TGF-β1 ( (15,26,27) and others [Pierre Coulie, personal communication]). Signal transduction through SMAD2/3 or via TGFβRII interaction may thus be artifacts caused by contaminating TGF-β1 rather than by GDF-15 itself (7,52,144). Therefore, studies reporting TGF-β related effects induced by recombinant human GDF-15 need to be regarded with great caution.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Likely, during 1.9 years of follow-up, an annual rate of stroke or systemic embolic events was 2.03% in AF patients with GDF-15 in the highest quartile (>2052 ng/L) while 0.90% in the lowest quartile (≤977 ng/L) in ARISTOTLE trial [45]. Mechanistically, on the one hand, systemic in ammation especially IL-1β, IL-6 and TNF-α was a potential mechanism promoting the formation of cerebral cardioembolism [46] and GDF-15 was proved related to them [47] [48]. On the other hand, AF, HF, CAD were one of the precondition of cardioembolic strokes which were a liated to augment of serum GDF-15 [49].…”
Section: Discussionmentioning
confidence: 99%